2019
DOI: 10.1161/jaha.118.010332
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Wall Tension Leads to Reduced miR‐133a in the Thoracic Aorta by Exosome Release

Abstract: Background Reduced miR‐133a was previously found to be associated with thoracic aortic ( TA ) dilation, as seen in aneurysm disease. Because wall tension increases with vessel diameter (Law of Laplace), this study tested the hypothesis that elevated tension led to the reduction of miR‐133a in the TA . Methods and Results Elevated tension (1.5 g; 150 mm Hg) applied to murine TA ex vivo reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 53 publications
2
9
0
Order By: Relevance
“…According to the findings found in our study, the origin of the uterine artery is in the same proportion as that reported in the previously described literature (Wu et al, 2007;Akerman, 2019;Barodka et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…According to the findings found in our study, the origin of the uterine artery is in the same proportion as that reported in the previously described literature (Wu et al, 2007;Akerman, 2019;Barodka et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…The article [103] directly reviews intercellular communication mediated by exosomes during vascular remodeling, including aneurysms. A number of recent studies also demonstrate evidence of the involvement of exosomes in the development of vascular aneurysms [104][105][106][107].…”
Section: Molecular Mechanisms Of Fibrogenesis and Mitochondrial Dysfu...mentioning
confidence: 94%
“…Lipids ( e.g. , ceramide), cell type, culture conditions, and the genomic health of the cell exhibit a correlation with the biogenesis of exosomes 32 , 45 , 46 , 47 , 48 , 49 , 50 . Diverse proteins are also involved in the regulation of exosome biogenesis and secretion.…”
Section: The Biogenesis Secretion Transportation and Uptake Of Evsmentioning
confidence: 99%